Additional file 4 of Immune cell-resolved transcriptomics provides insights into the basis for variations of fish genetic resistance to viral disease - Thomas C. Clark (13318734) (2025)
Additional file 4. Table S4—Single cell transcriptomic analysis of head kidney leukocytes.